A review of Brazilian Trimezia Salisb. Ex Herb., Iridaceae - Chukr, Nádia S.; Giulietti, Ana Maria (SITIENTIBUS série Ciências Biológicas, 2008)
The genus Trimezia is characterized by having herbs with low or medium size, plane or terete leaves with underground system in the form of a corm covered by spireled fibrous cataphylls. The floral morphology is vey distinctive, showing revolute internal tepal densely covered by stipes and trifide or bifide styles. The genus has a present 18 valid species and is distributed in tropical or subtropical regions of the American continent, especially in central Brazil. In this country, 13 species occur, 10 of them being endemic to Brazil and three occuring also in parts of Central America, Venezuela, Peru, Colombia, Argentina and Paraguay. Trimezia has its genetic diversity in “campos rupestres” vegetation of Minas Gerais, were nine species occur, seven of them occuring on more than one mountain, but Trimezia fistulosa is endemic of Serra do Cipó and T. plicatifolia is endemic to Serra do Cabral.